Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1976
DOI: 10.1063/1.432454
|View full text |Cite
|
Sign up to set email alerts
|

Spectra and structure of organophosphorus compounds. XV. Microwave spectrum of ethylphosphine

Abstract: The microwave spectra of CH3CH2PH2, CH3CH2PHD, and CH3CH2PD2 have been recorded in the range 18.0 to 40.0 GHz. A-type transitions were observed and assigned for both gauche and trans conformers of ethylphosphine, and b-type transitions observed and assigned for the gauche conformer. The dipole moment components for the gauche conformer were determined from the Stark effect to be: ‖μa‖= 0.86±0.01, ‖μb‖=0.73±0.07, ‖μc‖=0.45±0.05, and ‖μt‖=1.22±0.07 D. For the trans conformers, there was only one component of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…17,19 Also listed in Table V are the C u P and/or C u C bond lengths present in other simple molecules. [28][29][30][31][32][33][34][35][36][37][38][39][40] The nature of the bonds between these atoms, i.e., single, double, or triple bonds, is illustrated in the first column. From the table, the range in bond lengths for a carbon-phosphorus single bond is 1.86-1.88 Å, 1.65-1.68 Å for a double bond, and a C w P triple bond is 1.54-1.59 Å.…”
Section: Discussionmentioning
confidence: 99%
“…17,19 Also listed in Table V are the C u P and/or C u C bond lengths present in other simple molecules. [28][29][30][31][32][33][34][35][36][37][38][39][40] The nature of the bonds between these atoms, i.e., single, double, or triple bonds, is illustrated in the first column. From the table, the range in bond lengths for a carbon-phosphorus single bond is 1.86-1.88 Å, 1.65-1.68 Å for a double bond, and a C w P triple bond is 1.54-1.59 Å.…”
Section: Discussionmentioning
confidence: 99%
“…22 The results are shown in Table 1 together with the rotational constants of the EG conformer determined from L i ' s microwave experimental data." The agreement between the observed and calculated rotational constants suggests that the assumed structure is reasonable.…”
Section: Resultsmentioning
confidence: 99%
“…We hoped to be able to compare the potential function governing internal rotation around the C-P bond of isopropylphosphine with that determined for the similar bond in ethylphosphine. 3 The results of this study are reported herein.…”
Section: Introductionmentioning
confidence: 83%
“…The barriers to internal rotation of the methyl groups are in good agreement with those found by Durig et alu in a series of isopropyl compounds and show the expected upward trend when compared to the methyl torsional barriers found in ethylphosphine. 3 Clearly the problem of significant interest in this study is the determination of the more stable molecular conformation.…”
Section: Discussionmentioning
confidence: 99%